AN ANALYSIS OF HIGH ORDER THINKING SKILL (HOTS) IN ENGLISH QUESTIONS OF JUNIOR HIGH SCHOOL NATIONAL EXAMINATION 2018/2019 - Ade Dama Yanti; Rika Rika; Tiarnita Maria Siregar (Universitas Negeri Medan, 2021)
AN ANALYSIS OF HIGH ORDER THINKING SKILL (HOTS) IN ENGLISH QUESTIONS OF JUNIOR HIGH SCHOOL NATIONAL EXAMINATION 2018/2019 *Ade Dama Yanti **Rika, S.Pd., M.Hum. **Tiarnita Maria Sarjani Br. Siregar, S.Pd., M.Hum. ABSTRACT Ade Dama Yanti. 2161121001. An Analysis of High Order Thinking Skill (HOTS) in English Questions of Junior High School National Examination 2018/2019. A Thesis. English Education Program. State University of Medan, 2020. This study aimed to find out the level of thinking skills and to describe out the thinking skills distributed in English National Examination for Junior High School academic year 2018/2019 based on HOTS of Revised Taxonomy Bloom (2001). There are three level thinking skills in HOTS, the first is anyze skill which has the subskills of differentiating, organizing, and attributing. The second is evalute skill which has the subskills of checking and critiquing. The third is create skill which has the subskills of generating, planning, and producing. In solving the problems, this study used descriptive qualitative method. The data were obtained through documentation. There were four packages of the English National Examination which consisted of 50 questions in every package. The total of the questions were 200 questions. In analyzing the data, the researcher used the techniques of observation and the documentary analysis. The findings showed that the four packages applied analyze skill and evaluate skill of HOTS which were 18,5% of analyze skill and 4% of evaluate skill out of 200 questions. While for the distribution of the subskills, for the analyze skill had all the subskills except the differetiating skill and for the evaluate skill had all the subskills in the questions of the four packages. Keywords: English Questions, HOTS, National Examination